After Liberalism - Kolozova, Katerina (Identities: Journal for Politics, Gender and Culture, 2022)
Author(s): Katerina Kolozova Title (English): After Liberalism Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 19, No. 1-2 (2022). Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 40-47 Page Count: 7 Citation (English): Katerina Kolozova, "After Liberalism,” Identities: Journal for Politics, Gender and Culture, Vol. 19, No. 1-2 (2022): 40-47. Author Biography Katerina Kolozova, Institute of Social Sciences and Humanities, Skopje Dr. Katerina Kolozova is Executive Director, senior researcher and full professor at the Institute of Social Sciences and Humanities, Skopje, and a professor of political philosophy at FMK-Belgrade. She has published many influential articles in a number of international journals, as well as several books. These include: Capitalism’s Holocaust of Animals: A Non-Marxist Critique of Capital, Philosophy and Patriarchy (Bloomsbury Academic), as well as Cut of the Real: Subjectivity in Poststructuralist Philosophy (Columbia University Press).